HUKUMAN MATI BAGI TERPIDANA NARKOBA MENURUT HUKUM POSITIF DAN HUKUM PIDANA ISLAM - Yandi Maryandi (Prodi Hukum Keluarga Islam (Ahwal Asy-Syakhsiyyah) Fakultas Syariah Unisba, 2020)
ABSTRACTIn Indonesia, provisions regarding criminal acts are regulated by Law Number 35 of 2009 concerning Narcotics and Law Number 5 of 1997 concerning Psychotropics. In this Law, there are several criminal sanctions for criminals, such as imprisonment, fines and capital punishment. Regarding criminal sanctions (one of which is in Number 35 of 2009 concerning Narcotics) there are pros and cons from experts regarding this matter. One of the most severe forms of death penalty and has been debated for hundreds of years by criminal law and criminology experts. Narcotics in the context of Islamic law is a matter of ijtihâdî, because drugs do not enter directly into their prohibition by the texts of either the Al-Qur'an or al-Sunnah, and were not known at the time of the Prophet Muhammad at that time who were in the community from khamr drinkers. The research objective is to find out about the sanctions for the perpetrators of drug crime from the perspective of positive law and Islamic criminal law. The research methodology used is qualitative research through literature study, with the type of juridical normative research. The application of criminal sanctions given to manufacturers, dealers and dealers in accordance with Law No.35 of 2009 on Narcotics. The law on narcotics is haram as well as related to the haram of khamr, one of the penal sanctions is the death penalty using the hirabah approach because of the effects of narcotics from all aspects. Keywords: Drugs, Criminal Death, Islamic Criminal